Toxic effects of three essential oils on Ceratitis capitata - Miguel, Maria Graça (2014)
The effects of different essential oils, rich in oxygen-containing monoterpenes, isolated from three aromatic plants largely spread in Algarve (southern Portugal) were observed on Ceratitis capitata adults. The isolation of the essential oils were carried out by hydrodistillation and analyzed by GC and GC-MS. The most effective, in terms of mortality rate, was the oil of Mentha pulegium, mainly constituted by menthol, menthone, isomenthone and pulegone. Over 90 % of mortality was achieved after 48 hours of exposure to this essential oil. The remaining oils were not so effective, though always significantly superior to the control. They were mainly constituted by carvacrol (Thymbra capitata) and 1,8-cineole (Thymus albicans). It remains to clarify if the toxicity is due to a fumigant effector oral toxicity of the essential oils of M. pulegium and Thymbra capitata, as soon after the exposure, the Mediterranean fruit fly showed evident signs of loss of motor coordination and difficulty in flying.